Progressive taxation and tax morale - Philipp Doerrenberg; Andreas Peichl (Institute for the Study of Labor (IZA), 2010)
As the link between tax compliance and tax morale is found to be robust, finding the determinants of tax morale can help to understand and fight tax evasion. In this paper we analyze the effect of progressive taxation on tax morale in a cross-country approach - which has not been investigated before. Our theoretical analysis leads to two testable predictions. First, an individual's tax morale is higher, the more progressive the tax schedule is. Second, the impact of tax progressivity on tax morale is declining in income. In our empirical analysis, we make use of a unique dataset of tax progressivity measures and follow most of the tax morale literature by employing the World Values Survey to measure tax morale. Controlling for a wide range of variables, we confirm both hypotheses in our empirical analysis.
Keywords: H26; H24; D7; D31; 330; tax morale; tax compliance; progressivity; taxation; redistribution